EVALUASI SALURAN DRAINASE DAN LAJU RESAPAN AIR TANAH DI JALAN VILAKU INDAH, KELURAHAN SURAU GADANG, KOTA PADANG - Rino Fajar Ramadhan; Totoh Andayono (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Waterlogging problems in urban areas are generally caused by the inability of drainage systems to accommodate runoff discharge and are also influenced by soil infiltration characteristics. Jalan Vilaku Indah, Surau Gadang Subdistrict, Padang City, is one of the areas that frequently experiences inundation during rainfall events. This study aims to evaluate the performance of the existing drainage system and to analyze the soil infiltration rate in controlling waterlogging. The methods employed include hydrological analysis to determine design rainfall and design flood discharge, hydraulic analysis using EPA SWMM 5.2 software, and soil infiltration rate testing using the double ring infiltrometer method at nine test locations. The results of the hydrological analysis indicate that the 50-year return period design flood discharge (Q50) is 0.067 m³/s. The hydraulic simulation results using EPA SWMM show that in several channel segments, the water level rises beyond the storage capacity, with the simulated peak discharge reaching approximately 0.097 m³/s, thereby causing overflow and inundation on the roadway. The infiltration test results indicate that the final infiltration capacity (Fc) ranges from 48 mm/h to 192 mm/h, with an average value of 101.33 mm/h, which is classified as a fast infiltration class. These findings indicate that the waterlogging problems at the study site are caused by the limited capacity of the existing drainage system and changes in land use.Keywords: urban drainage, design flood discharge, infiltration rate, EPA SWMM.